Intratracheal inoculation results in Brucella-associated reproductive disease in male mouse and guinea pig models of infection - Hensel, Martha E.; Stranahan, Lauren W.; Edwards, John F.; Arenas-Gamboa, Angela M. (Frontiers in Microbiology, 2022)
1 Brucella species are considered a significant cause of reproductive pathology in male and female animals. Importantly, Brucella melitensis can induce reproductive disease in humans. Reproductive pathogenesis and evaluation of newly developed countermeasures against brucellosis studies have traditionally utilized female animal models. However, any potential, new intervention for use in humans would need to be evaluated in both sexes. Therefore, animal models for male reproductive brucellosis are desperately needed to understand disease progression. Accordingly, we evaluated guinea pigs and mice using B. melitensis 16M in an intratracheal model of inoculation at different stages of infection (peracute, acute, and chronic) with an emphasis on determining the effect to the male reproductive organs. Aerosol inoculation resulted in colonization of the reproductive organs (testicle, epididymis, prostate) in both species. Infection peaked during the peracute (1-week post-infection [p.i.]) and acute (2-weeks p.i.) stages of infection in the mouse in spleen, epididymis, prostate, and testicle, but colonization was poorly associated with inflammation. In the guinea pig, peak infection was during the acute stage (4-weeks p.i.) and resulted in inflammation that disrupted spermatogenesis chronically. To determine if vaccine efficacy could be evaluated using these models, males were vaccinated using subcutaneous injection with vaccine candidate 16M∆vjbR at 10^9 CFU/100 µl followed by intratracheal challenge with 16M at 10^7. Interestingly, vaccination efficacy varied between species and reproductive organs demonstrating the value of evaluating vaccine candidates in multiple models and sexes. Vaccination resulted in a significant reduction in colonization in the mouse, but this could not be correlated with a decrease in inflammation. Due to the ability to evaluate for both colonization and inflammation, guinea pigs seemed the better model not only for assessing host-pathogen interactions but also for future vaccine development efforts.